Catheter reconstruction and dosimetric verification of MRI-only treatment planning (MRTP) for interstitial HDR brachytherapy using PETRA sequence. (7th February 2023) - Lee, Casey Y; Kaza, Evangelia; Harris, Thomas C; O'Farrell, Desmond A; King, Martin T; Dyer, Michael A; Cormack, Robert A; Buzurovic, Ivan
Abstract: Objective . The feasibility of MRI-only treatment planning (MRTP) for interstitial high-dose rate (HDR) brachytherapy (BT) was investigated for patients diagnosed with gynecologic cancer. Approach . A clinical MRTP workflow utilizing a 'pointwise encoding time reduction with radial acquisition (PETRA)' sequence was proposed. This is a clinically available MRI sequence optimized to improve interstitial catheter-tissue contrast. Interstitial needles outside the obturator region were reconstructed using MR images only. For catheters penetrating through the obturator, a library-based reconstruction was proposed. In this work, dwell coordinates from the clinical CT-based reconstruction were used as the surrogate for the library-based approach. For MR-only plan, dwell times were activated and assigned as in the clinical plans. The catheter reconstruction was assessed by comparing dwell position coordinates. The dosimetric comparisons between a clinical plan and MR-only plan were assessed for physical and EQD2 dose and volume parameters for D 90, D 50 and D 98 for clinical target volume (CTV) and D 2cc, D 0.1cc and D 5cc for OARs. Main results . Catheter reconstruction was possible using the optimized PETRA sequence on MR images. An overall reconstruction difference of 1.7 ± 0.5 mm, attributed to registration-based errors, was found compared to the CT-based reconstruction. The MRTP workflow has the potential to generate a treatment plan with an equivalent dosimetric quality compared to the conventional CT/MRI-based approach. For CTV D 90, physical and EQD2 dose and volume parameter differences were 1.5 ± 1.9% and 0.7 ± 1.0 Gy, respectively. For D 2cc OARs, DVH (EQD2) differences were −0.4 ± 1.1% (−0.2 ± 0.5 Gy), 0.5 ± 2.8% (0.2 ± 1.3 Gy) and −0.5 ± 1.4% (−0.2 ± 0.5 Gy) for rectum, bladder, and sigmoid, respectively. Significance . With the proposed MRTP approach, CT imaging may no longer be needed in HDR BT for interstitial gynecologic treatment. A proof-of-concept study was conducted to demonstrated that MRTP using PETRA is feasible, with comparable dosimetric results to the conventional CT/MRI-based approach.